2013
DOI: 10.1007/s00221-013-3549-6
|View full text |Cite
|
Sign up to set email alerts
|

“Self pop-out”: agency enhances self-recognition in visual search

Abstract: distractors increased reaction times despite being more perceptually different than the spatial distractors. the findings demonstrate the importance of agency in self-recognition and self-other discrimination from movement in social settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 49 publications
(35 reference statements)
1
44
1
Order By: Relevance
“…The VR literature contains many examples in which users take on virtual bodies that function differently than their physical world bodies. For example, Salomon, Lim, Kannape, Llobera, and Blanke (2013) used VR to examine participants' ability to recognize their avatar after delaying the avatars' movements from their physical world movements. As mentioned previously, Banakou, Groten, and Slater (2013) showed that embodying a child avatar influences adult users' perception of size.…”
Section: Discussionmentioning
confidence: 99%
“…The VR literature contains many examples in which users take on virtual bodies that function differently than their physical world bodies. For example, Salomon, Lim, Kannape, Llobera, and Blanke (2013) used VR to examine participants' ability to recognize their avatar after delaying the avatars' movements from their physical world movements. As mentioned previously, Banakou, Groten, and Slater (2013) showed that embodying a child avatar influences adult users' perception of size.…”
Section: Discussionmentioning
confidence: 99%
“…SoA has been suggested to be a basic mechanism allowing segregation of the self from the environment and conspecifics (Jeannerod, 2003;Salomon, 2017;Salomon, Lim, Kannape, Llobera, & Blanke, 2013;Tsakiris, Haggard, Franck, Mainy, & Sirigu, 2005). While volitional changes of self-other boundaries may have positive emotional effects (see, e.g., Colzato et al, 2012), unsolicited and temporally extended loss of SoA over one's actions may cause an unwilled reduction in self-other segregation, resulting in psychosis-like symptoms (Blanke et al, 2014;Salomon, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…body ownership [5][8]. Sense of body ownership also depends on the integration of motor signals [9][12], which by interaction with tactile perception, as in the case of self-touch, contributes to the self-awareness [13].…”
Section: Introductionmentioning
confidence: 99%